Pelaksanaan Clinical Decision Support System Pada Rekam Medis Elektronik di Klinik Pendidikan UPT Poliklinik Politeknik Negeri Jember: Literature Review - Yuli Qodariyah; Lay Arif Firiandri Yulius; Sheila Stefani; Vidia Andita Sari; Novita Rahayu; Vip Paramarta (Madani: Jurnal Ilmiah Multidisiplin, 2023)
The introduction of Electronic Medical Records (EMR) along with Clinical Decision Support Systems (CDSS) has brought about significant changes in healthcare services. This research focuses on the implementation of EMR and CDSS in an educational clinic in Jember Regency, Indonesia. The implementation method used is "Parallel implementation," where EMR is introduced alongside the existing paper-based medical records system until a complete transition to the electronic system. Respondents included doctors, registration officers, nurses, and pharmacy staff.The research findings indicate that EMR with CDSS facilitates patient registration, provides recommendations for diagnosis and treatment, and monitors patient risk factors. CDSS applications, including DOQ-IT, play a crucial role in supporting healthcare professionals in making real-time medical decisions. This study highlights the importance of awareness and understanding among healthcare professionals in adopting EMR with CDSS technology. Training, education, and the active involvement of healthcare personnel are identified as key factors in overcoming implementation challenges. Therefore, the development of EMR with CDSS in Indonesia holds the potential to enhance healthcare service quality, patient safety, and open avenues for research and innovation in the healthcare technology sector.